Potential Bromelain Pinneapple Extract to Breaker Tempe Protein As Organic MSG - Tias, Eriza Putri Ayu Ning; Wicaksono, M. Galih; Hayati, Lu'lu'ul Rosyiqul; Salsabila, Aulia Firda; Prabowo, Kus Alan Dhimas; Setyaningsih, Endang (Lighthouse Publishing, 2022)
New alternatives are needed to change flavorings from chemicals to organic so that they do not have a bad impact on health. The study's results proved that giving MSG at a dose of 9 g / day to red blood cells caused the appearance of a micronucleus so that it indicated a mutagenic MSG. The potential of bromelin enzyme contained in pineapple fruit is able to break down proteins from tempe so that it can give rise to a savory taste that is generally found from other flavorings. The purpose of this study was to determine the potential of bromelin extract pineapple, which is a tempe protein breaker as an organic flavoring sourced from various literatures. The research was conducted using a literature review method of reference sources such as google scholar and research gate. A total of 40 articles were found and then selected based on predetermined parameters resulting in 25 selected articles. From the results of the literature search obtained a percentage of 80% for the sampling method on the extraction method, 16% centrifuged and the method using extraction and centrifugation 4%. Meanwhile, judging from the variables studied, 52% were obtained regarding the activity of hydrolyzing proteins, 12% for the characterization of the enzyme bromelin, 8% for the mechanism of action of bromelin as an anti-bacterial and 4% in the stacking of meat, catalyzing peptide bonds, mobilization of bromelin enzymes, meat quality, decreased glucose levels, healing of lukan and physical quality of cheese curd. And when viewed from the part of the pineapple plant that is utilized 44% of the flesh of the pineapple fruit, 12% of the pineapple weevil, 8% each of the flesh of the fruit and the fruit weevil of the fruit, the skin of the pineapple fruit and the flesh of the young pineapple fruit and 4% each of the ripe pineapple weevil, the flesh of the ripe fruit, the stem and the final leaf of the pineapple plant. And when viewed from the use of the benefits of bromelin, a score of 36% was obtained to increase protein levels in the product, 20% to speed up the hydrolysis process, 12% to stack meat, 8% to inhibit streptococcus bacteria, and 4% each was used to hydrolyze collagen. Helps the fermentation process, anti-browning agents fund therapeutic genes.